2009
DOI: 10.1042/bj20081575
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf1 CNC/bZIP protein is a nuclear envelope-bound transcription factor that is activated by t-butyl hydroquinone but not by endoplasmic reticulum stressors

Abstract: In rat liver RL-34 cells, endogenous Nrf1 (nuclear factor-erythroid 2 p45 subunit-related factor 1) is localized in the ER (endoplasmic reticulum) where it exists as a glycosylated protein. Electron microscopy has demonstrated that ectopic Nrf1 in COS-1 cells is located in the ER and the NE (nuclear envelope). Subcellular fractionation, together with a membrane proteinase protection assay, revealed that Nrf1 is an integral membrane protein with both luminal and cytoplasmic domains. The N-terminal 65 residues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
147
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(176 citation statements)
references
References 58 publications
27
147
2
Order By: Relevance
“…Both proteins are glycosylated in the ER and are also located in the nuclear envelope. Interestingly, although Nrf1 is also targeted to the ER and located in the nuclear envelope (32), our data suggest that Nrf3 is integrated into membranes in a more complete fashion. Proteinase protection assays have shown that the topology of Nrf3 within the membrane is modulated by NHB2 within the NTD.…”
Section: ⌬2-75mentioning
confidence: 88%
“…Both proteins are glycosylated in the ER and are also located in the nuclear envelope. Interestingly, although Nrf1 is also targeted to the ER and located in the nuclear envelope (32), our data suggest that Nrf3 is integrated into membranes in a more complete fashion. Proteinase protection assays have shown that the topology of Nrf3 within the membrane is modulated by NHB2 within the NTD.…”
Section: ⌬2-75mentioning
confidence: 88%
“…Antiserum raised in rabbits against recombinant mouse Nrf1 protein (i.e., mNrf1␤, residues 293 to 742) has been described previously (25). However, in the present study, this serum was immunopurified prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Nrf1 localizes primarily to the ER (see Figure 1) as well as the nuclear envelope membrane [11]. The ER membrane-resident form of Nrf1 represents a low activity, glycosylated protein with an apparent molecular weight of 120 kDa (p120), while the nuclear form (p95) is an active, non-glycosylated (or deglycosylated) protein [15, see also Figure 1].…”
Section: Introductionmentioning
confidence: 99%
“…The ER membrane-resident form of Nrf1 represents a low activity, glycosylated protein with an apparent molecular weight of 120 kDa (p120), while the nuclear form (p95) is an active, non-glycosylated (or deglycosylated) protein [15, see also Figure 1]. The ER location of Nrf1 is thought to be suitable for the maintenance of the ER redox homeostasis [11], perhaps by affecting the ER membrane lipid organization via its amphipathic, transmembrane α-helices and participating in membrane-dependent biological events [16]. It has also been proposed that the localization of Nrf1 within the ER determines the activity of this CNC factor and that the ER redox status and Nrf1 glycosylation status could cause Nrf1 to relocate from the ER to the nucleus [11].…”
Section: Introductionmentioning
confidence: 99%